Dividing justly in Bargaining Problems with Claims - Simon Gächter; Arno Riedl (Tinbergen Institute, 2004)
Theoretical research on claims problems has concentrated on normative properties and axiomatizations of solution concepts. We complement these analyses by empirical evidence on the predictability of three classical solution concepts in a bankruptcy problem. We examine both people's impartial normative evaluations as well as their actual negotiation behavior in a bargaining with claims environment. We measure people's judgments on the normative attractiveness of solution concepts with the help of a survey and also observe actual agreements in a bargaining experiment with real money at stake. We find that the proportional solution is the normatively most attractive rule, whereas actual negotiation agreements are closest to the 'constrained equal award' solution.
Keywords: D63; C78; C92; 330; Bankruptcy problems with claims; proportional rule; equal-awards rule; equal-losses rule; fairness; laboratory experiment; vignette; Insolvenzverwaltung; Gerechtigkeit; Verhandlungstheorie